Determination of car seat contact area for personalised thermal sensation modelling - Fojtlín, Miloš; Psikuta, Agnes; Toma, Róbert; Fišer, Jan; Jícha, Miroslav (PLoS One, 2018)
A lot of daily activities are conducted in a sedentary posture. This includes a thermal interaction between the human and the seat that has implications on thermal perception and comfort. These interactions are investigated by simulating heat and mass transfer, thus, reducing a need for costly and time demanding subject studies. However, it is not clear, from the available literature, what portion of the body surface area is actually affected by the seat with respect to human anthropometry. The aim of this study was to develop a predicting function of the seat contact area based on anthropometric parameters. The results showed strong linear correlation between the contact area obtained by printing a body silhouette on paper placed at the seat and body weight, height, body surface area, and body mass index. The body surface area and the body weight were identified as the best predictors for the contact area.
Keywords: ženské pohlaví; dospělí; mužské pohlaví; Pressure; Female; tělesná hmotnost; Adult; lidé; Equipment Design; Body Weight; Humans; tlak; Ergonomics; vnímání teploty; ergonomie; Male; design vybavení; Thermosensing